Before and After the Reform: Fixed Line Internet Penetration in Mexican Households - Chico, María Catalina Ovando; Pérez, Emmanuel Olivera; Lara, Juan Carlos Bocarando (Law, State and Telecommunications Review, 2018)
Purpose ”“ Despite being the second largest mobile market in Latin America regarding subscribers, Mexico’s penetration levels remain lower than the regional averages. The aim of this paper is to evaluate whether the Mexican 2013 Telecommunications and Broadcasting Reform helped mitigate or exacerbate the digital divide. In particular, we evaluate if the Reform had an impact on fixed-line internet penetration in Mexico. Methodology/approach/design ”“ For the assessment, the 2010 Census and 2015 Intercensal Survey data used to create impact indexes through Generalized Linear Models (GLMs) estimations. Findings ”“ Through a quintile analysis were confronted by results, with the intention of showing the average of internet penetration in each income group. The data obtained suggest that internet penetration had positive variations in all the quintiles indicating that recent regulatory changes in telecommunications matter had helped to reduce the digital divide. Practical implications ”“ The poor and vulnerable groups remain at the digital exclusion; these groups need more digital inclusion actions.